Perbandingan Pendidikan di Irak dan Oman - Zaka Ardiansyah (Paedagogia: Jurnal Pendidikan, 2018)
The educational policy applied in a country has significant implications in education. The national educational goals of a country can be easily achieved if the state plays an active role in education. The active role is not only in the determination of curriculum and model of education, but also on the level of education budget and the direction of education policy in that country. This article discusses the comparison of education in two countries with the majority Muslim population, namely Iraq and Oman. This article is an online data-based study. The results of the study in this study concluded that the role of government is very urgent in determining the success of national education. Another conclusion of the comparison of education in the two countries is that education in both countries is not capitalist, and Education is not used as a business field to reap profits for the stakeholders.